What’s Missing - Navickas, Katrina (London Review of Books, 2018)
Capitalism is in crisis, again. Inequality, measured in wages, wealth distribution, employment, ‘affordable’ housing, has become the dominant framework for understanding the economy. Through this lens, people can extrapolate to the macroeconomic from their own individual experiences.
N/A
Keywords: MORAL Economists: R.H. Tawney; Karl Polanyi; E.P. Thompson & the Critique of Capitalism; The (Book); POLANYI LEVITT; Kari; POLANYI; Karl; 1886-1964; book review